Lagrangian Reconstruction to Extract Small‐Scale Salinity Variability From SMAP Observations. Issue 3 (22nd February 2021) - Barceló‐Llull, Bàrbara; Drushka, Kyla; Gaube, Peter
Abstract: As the resolution of observations and models improves, emerging evidence indicates that ocean variability on 1–200‐km scales is of fundamental importance to ocean circulation, air‐sea interaction, and biogeochemistry. In many regions, salinity variability dominates over thermal effects in forming density fronts. Unfortunately, current satellite observations of sea surface salinity (SSS) only resolve scales ≥40 km (or larger, depending on the product). In this study, we investigate small‐scale variability (≲25 km) by reconstructing gridded SSS observations made by the Soil Moisture Active Passive (SMAP) satellite in the northwest Atlantic Ocean. Using altimetric geostrophic currents, we numerically advect SMAP SSS fields to produce a Lagrangian reconstruction that represents small scales. Reconstructed fields are compared to in‐situ salinity observations made by a ship‐board thermosalinograph, revealing a marked improvement in small‐scale salinity variability when compared to the original SMAP fields, particularly from the continental shelf to the Gulf Stream. In the Sargasso Sea, however, both SMAP and the reconstructed fields contain higher variability than is observed in situ. Enhanced small‐scale salinity variability is concentrated in two bands: a northern band aligned with the continental shelfbreak and a southern band aligned with the Gulf Stream mean position. Seasonal differences in the small‐scale variability appear to covary with the seasonal cycle of the large‐scale SSS gradients resulting from the freshening of the coastal waters during periods of elevated river outflow. Plain Language Summary: Emerging evidence indicates that oceanic structures at scales smaller than ∼100 km have an important contribution to ocean circulation, air‐sea interactions, and biogeochemical cycling. In many regions, the contribution of salinity dominates that of temperature in generating density fronts. Satellites that measure sea surface salinity (SSS) from space have a resolution lower than 40 km and do not allow the observation of small‐scale structures (<25 km). The present work is motivated by the need to develop techniques to exploit satellite salinity measurements to extract signals with the highest possible spatial resolution. We investigate small‐scale variability captured in reconstructions of SSS observations made by the Soil Moisture Active Passive (SMAP) satellite in the northwest Atlantic Ocean. Reconstructed fields are compared to in‐situ observations, revealing a marked improvement in the reproduction of observed salinity fronts when compared to SMAP fields. Enhanced small‐scale salinity variability is found to be concentrated in two bands: a northern band aligned with the continental shelfbreak, and a southern band aligned with the Gulf Stream mean position. Seasonal differences in the small‐scale salinity variability are mainly driven by the seasonal cycle of the large‐scale SSS induced by the freshening of the coastal waters due to river outflow. Key Points: Reconstructed SSS shows realistic small‐scale variability near the Gulf Stream and an overestimation in the Sargasso Sea inherited from SMAP Enhanced small‐scale salinity variability is concentrated along the continental shelfbreak and the Gulf Stream mean position Seasonality of small‐scale salinity variability appears to be modulated by the annual cycle of large‐scale SSS